Assessing medical tour service towards tourist behavioral intention in Penang - Shaharuddin, Nuraini Syakirah; Md Sawari, Siti Salwa (2019)
Medical tourism received attention recently in global. Ongoing with the trends and interest in increasing the tourism development, medical tourism is marketed as a niche product that gives both medical services and tourism packages that related to the medical industry. The objective of this paper is to investigate medical tour service towards tourist behavioral intention in Penang. Through medical tourism, tourist can relief their anxiety and stress on their health problem because medical tour services consist of pleasure orientation. The study was carried out by conducting survey around 30 respondents who travel to get a medical tour service in Penang and the method used to analyse the level of tourist behavioural intention is by using SPSS. From the research, it is found that the medical factor which are affordability of price, medical quality, service swiftness is the most factor that influence tourist behavioral intention to visit Penang for the purpose of medical treatment.